NILAI NORMAL PEMERIKSAAN STATUS MENTAL NEUROLOGI STRUB DAN BLACK VERSI INDONESIA - Nastiti Widyarini, Silvia F. Lumempouw, Yetty Ramli, Herqutanto (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION STRUB AND BLACK MENTAL STATUS EXAMINATION OF NEUROLOGY SBMSEN IS AN INSTRUMENT THAT CAN BE USED TO DETECT COGNITIVE IMPAIRMENT THE INDONESIAN VERSION OF THIS EXAM HAS BEEN DEVELOPED BUT ITS NORMAL VALUES FOR NORMAL COGNITIVE INDONESIAN PEOPLE ARE STILL UNKNOWN